Investment Accounting Analysis and Its Impact on Nominal Investment Assets of DKI Jakarta Provincial Governmen - Abu Bakar (Politeknik Negeri Madiun, 2023)
This study aims to find out and understand how the recording of investment, investment gain, profit sharing, profit sharing realization and loss accounting. The research method used is descriptive. The results of the study show that capital investment accounting is recorded according to three investment valuation methods. 2) Profit sharing accounting is divided into three. Investment in BUMD, in third parties and in limited liability companies. The impact of this investment accounting application is that the nominal amount of investment value is always changing for BUMD and limited liability companies and remains for third parties 3) Realization of profit sharing for BUMD is recorded by debiting cash accounts and crediting investment receivables and from investments with third parties recorded by debiting estimates cash and crediting investment receivables to BUMD. 4) The accounting treatment of investment losses is influenced by inconsistent accounting policies in accounting policies and the classification of companies where they invest. The wrong classification causes the regional government's capital investment assets to decrease and harm the DKI Jakarta Provincial Government using the equity method and the value of capital investment to third parties using the cost method does not change at all as a Limited Liability Company